Diversity of Wickerhamomyces (Wickerhamomycetaceae, Saccharomycetales) in China with the description of four new species - Chai, Chun-Yue; Ke, Tao; Niu, Qiu-Hong; Hui, Feng-Li (Frontiers in Microbiology, 2024)
Wickerhamomyces is a well-known genus of the family Wickerhamomycetaceae in the class Ascomycetes. These fungi can survive in a variety of substrates and environments and perform many valuable roles in both industrial processes and the natural ecosystems. During our investigation of yeast diversity associated with plant materials, 53 Wickerhamomyces isolates were obtained from rotting wood and plant leaves collected in Fujian, Guizhou, Henan, and Yunnan Provinces of China. Isolates were identified as 14 Wickerhamomyces species, including one species known previously to occur in China (W. anomalus), nine new record species in China (W. arborarius, W. ciferrii, W. edaphicus, W. lynferdii, W. pijperi, W. subpelliculosa, W. xylosica, W. strasburgensis, and W. sydowiorum), and four novel species (W. guiyangensis sp. nov., W. paramyanmarensis sp. nov., W. quanzhouensis sp. nov., and W. phyllophilus sp. nov.). This study presents a detailed account of these new species, illustrating their morphology and analyzing their phylogenetic relationships with other Wickerhamomyces species. Our study is the first comprehensive study on Wickerhamomyces species associated with plant materials from tropical and subtropical China. Results of this study update our understanding of the phylogenetic relationships, systematics, and ecology of Wickerhamomyces.